Urinary bladder paraganglioma presenting with abdominal pain and elevated cardiac enzymes: a case report of atypical manifestations and diagnostic challenges - Zhou, Hong; Hu, Xiaohui; Yan, Qin (Frontiers in Oncology, 2025)
Urinary bladder paraganglioma (UBPGL) is a very rare neuroendocrine tumor, accounting for 0.05% of all bladder neoplasms. Classic symptoms include paroxysmal hypertension, palpitations, and sweating triggered by micturition. However, atypical presentations may complicate the diagnosis. This report describes the case of a 35-year-old woman who presented with persistent lower abdominal pain and isolated elevation of cardiac enzymes. Imaging revealed a pelvic mass initially suspected to be adnexal pathology. Emergency laparoscopy identified a retroperitoneal mass adjacent to the bladder and an endometriotic ovarian cyst. Postoperative pathology confirmed UBPGL, with immunohistochemistry positive for neuroendocrine markers (CD56, chromogranin-A, synaptophysin). Elevated cardiac enzymes and a prolonged QTc interval were observed preoperatively, likely secondary to catecholamine-induced myocardial injury, although biochemical confirmation was not available. The patient recovered uneventfully after resection of the tumor. This case highlights the potential for UBPGL to have atypical cardiovascular manifestations, including isolated elevation of cardiac enzymes without classic hypertensive crises. Such findings may reflect catecholamine-driven cardiomyocyte stress, emphasizing the need for heightened suspicion in cases that present with unexplained abdominal pain and cardiac abnormalities. Diagnostic challenges arise from overlapping symptoms with gynecologic emergencies and the rarity of preoperative biochemical testing in acute settings. UBPGL should be considered in patients with a pelvic mass accompanied by unexplained cardiac abnormalities. Early resection remains curative, but multidisciplinary evaluation, including biochemical screening for catecholamine excess, is critical to mitigate the cardiovascular risk. Long-term surveillance is warranted in view of the potential for metastasis. This case underscores the importance of including rare neuroendocrine tumors in the differential diagnoses for atypical abdominal presentations.